(3SfI GdJaGVd heG aVd Gddg Hg GdfSGA Ydi GdQLGd (B/s - (3GdYXe, YGHOI GdeDjOs; (3GdWfWGhj, Ydj eUWai eMeO,s 1327-1420 (3gLQjG(B.s ((3HjQhJ (B:s (3OGQ GHf MRe,s, 2000)
(3jJfGhd GdcJGH JaVjd GdPchQYf GdfSGA ef GdfGMjI GdESdGejI hCgejI GdeQCI hOhQgG(B.s
Keywords: (3GdeQCI GdeSdeIs